FEATURES OF THE INTEGRATED APPROACH OF THE ASSESSMENT EFFECTIVE СТИ PRODUCTIONS - T. G. Aygumov; E. A. Sultanova (Вестник Дагестанского государственного технического университета: Технические науки)
In article features of an integrated approach of an efficiency evaluation of production taking into account economic, ecological and social its components are considered.